Graphene as a Tunable Anisotropic or IsotropicPlasmonic Metasurface - Huidobro,PA; Kraft,M; Maier,SA; Pendry,JB (ACS Nano, 2016)
We demonstrate a tunable plasmonic metasurface by considering a graphene sheetsubject to a periodically patterned doping level. The unique optical properties ofgraphene result in electrically tunable plasmons that allow for extreme confinementof electromagnetic energy in the technologically significant regime of THz frequencies.Here we add an extra degree of freedom by using graphene as a metasurface, proposingto dope it with an electrical gate patterned in the micron or sub-micron scale. Byextracting the effective conductivity of the sheet we characterize metasurfaces periodicallymodulated along one or two directions. In the first case, and making use of theanalytical insight provided by transformation optics, we show an efficient control ofTHz radiation for one polarization. In the second case, we demonstrate a metasurfacewith an isotropic response that is independent of wave polarization and orientation.